Pretreatment With Fragments of Substance-P or With Cholecystokinin Differentially Affects Recovery From Sub-Total Nigrostriatal 6-Hydroxydopamine Lesion - S. Nikolaus; J. P. Huston; R. K. W. Schwarting (Neural Plasticity)
The neuropeptide substance P is known to have mnemogenic and reinforcing actions and can exert neurotrophic and regenerative effects in vitro as well as in vivo. Furthermore, our previous work in the rat showed that either pre- or post-lesion treatment with substance P can promote functional recovery in cases of partial nigrostriatal dopamine lesions. Other work has provided evidence that the effects of substance P might be differentially encoded by its C- and N-terminal fragments. The C-terminal fragment was found to be reinforcing, whereas the mnemogenic as well as neurotrophic properties have been ascribed to the N-terminal sequences. Given these relations, we asked here whether pre-lesion treatment with either a C- or an N-terminal fragment of substance P might differentially affect the behavioral and neurochemical outcome of nigrostriatal dopamine lesions. Therefore, either substance P1−7 or substance P5−11 (37 nmol/kg each) was administered intraperitoneally daily for eight consecutive days before unilateral 6-hydroxy-dopamine lesions of the substantia nigra. Control rats received prelesion treatment with vehicle. Furthermore, we investigated the effects of pre-treatment with Boc-cholecystokinin-4 (0.91 nmol/kg), as we had found an increase in dopamine metabolism in animals that were pre-treated with cholecystokinin-8 in a former study. In accordance with our previous work, drug treatment effects were observed when excluding animals with most severe dopamine lesions: In animals with partial lesions (residual neostriatal dopamine levels of more than 10%), lesion-dependent asymmetries in turning behavior were observed in animals that were pre-treated with vehicle-, substance P1−7 , or Boc-cholecysto-kinin–4,. whereas turning after pre-treatment with substance P5−11 was not significantly asymmetrical. Furthermore, the ipsi- and contra-lateral neostriatal dopamine levels did not differ significantly in this group. Moreover, pre treatment with substance P5−11 affected dopamine metabolism in the neostriatum and in the venral striatum, as indicated by increased ratios of dihydroxyphenyllic acid to dopamine. The data provide the first evidence that the promotive effects of substance-P treatment in the unilateral dopamine lesion model might be mediated by its C-terminal and might depend on actions on residual dopamine mechanisms.